How we fall apart: Similarities of human aging in 10 European countries - Ana Lucia Abeliansky; Holger Strulik (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2017)
We analyze human aging, understood as health deficit accumulation, for a panel of European individuals. For that purpose, we use four waves of the Survey of Health, Aging and Retirement in Europe (SHARE dataset) and construct a health deficit index. Results from log-linear regressions suggest that, on average, elderly European men and women develop about 2.5 percent more health deficits from one birthday to the next. In non-linear regression (akin to the Gompertz-Makeham model), however, we find much greater rates of aging and large differences between men and women as well as between countries. Interestingly, these differences follow a particular regularity (akin to the compensation effect of mortality). They suggest an age at which average health deficits converge for men and women and across countries.
Keywords: I10; I19; 330; health; aging; health deficit index; Europe; gender differences; compensation law; human life span